Comparison of Total Phenolic Content and Antioxidant Activity of Some Gluten-Free Flour (Aintelia Science Notes, 2022)
People suffering from gluten-related disorders must follow a lifelong gluten-free diet. Therefore, scientists, health experts, and food manufacturers are evaluating different ingredients to develop gluten-free formulations that are superior in terms of nutritional, sensorial, and functional aspects. This study aimed to compare the total phenolic content (TPC) and antioxidant activity of some gluten-free flour sold on the market. Almond, coconut, quinoa, teff, tapioca, and white mulberry flour samples were analyzed in terms of TPC by the Folin-Ciocalteu method using gallic acid (GA) as standard, and antioxidant activity with the 2,2-diphenyl- 1-picrylhydrazyl (DPPH) and 2,2'-azino-bis-(3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) radical scavenging assays. The TPC of tapioca, coconut, almond, teff, quinoa, and white mulberry flour samples were determined as 0.673±0.014, 1.634±0.031, 2.223±0.057, 2.869±0.033, 4.076±0.054, and 9.973±0.361 mg GAE/g dry weight, respectively. The antioxidant activity of tapioca, coconut, almond, teff, quinoa, and white mulberry flour samples in terms of DPPH assay was found as 0.731±0.084, 1.343±0.105, 2.182±0.132, 2.778±0.077, 2.168±0.117, and 5.513±0.073 mg TE/g dry weight, respectively. On the other hand, the data obtained in the ABTS assay for the same samples were 0.260±0.013, 0.616±0.037, 1.233±0.053, 0.925±0.036, 0.819±0.039, and 2.315±0.050 mg TE/g dry weight, respectively. Moreover, a positive relation between TPC and antioxidant activity (DPPH and ABTS) was observed for flour types by Pearson’s correlation coefficient, which varied between 0.790 and 0.984 (p